A history of women's menstruation from ancient Greece to the twenty-first century: Psychological, social, medical, religious, and educational issues - Hufnagel, Glenda Lewin (Edwin Mellen Press, 2012)
Keywords: approches et analyses; corps; discipline; histoire; histoire et politique; menstruations; patriarcat; projet charge mentale; pédagogie; santé; santé menstruelle; sciences humaines; systèmes d'oppressions; thématiques; violences; violences envers les femmes*

Anti-porn: the resurgence of anti-pornography feminism - Long, Julia (Zed Books, 2012)
"Anti-porn feminism is back. Countering the ongoing 'pornification' of Western culture and society, with lads' mags on the middle shelf and lap-dancing clubs in residential areas, anti-porn movements are re-emerging among a new generation of feminist activists worldwide. This essential new guide to the problems with porn starts with a history of modern pro and anti political stances before examining the ways in which the new arguments and campaigns around pornography are articulated, deployed and received. Drawing on original ethnographic research, it provides an in-depth analysis of the groups campaigning against the pornography industry today, as well as some eye-opening facts about the damage porn can do to women and society as a whole. This unique and inspiring book explains the powerful comeback of anti-porn feminism, and it controversially challenges liberal perspectives and the mainstreaming of a porn culture that threatens to change the very nature of our intimate relationships"--Résumé de l'éditeur.
Keywords: approches et analyses; corps; cours; discipline; féminisme anti-porn; féminisme pop; militance; patriarcat; premier cycle; sex1911; sexualité; systèmes d'oppressions; thématiques